Relationship between social support during pregnancy and postpartum depressive state: a prospective cohort study - Morikawa, Mako (Sci Rep, 2015)
Although the association between social support and postpartum depression has been previously investigated, its causal relationship remains unclear. Therefore, we examined prospectively whether social support during pregnancy affected postpartum depression. Social support and depressive symptoms were assessed by Japanese version of Social Support Questionnaire (J-SSQ) and Edinburgh Postnatal Depression Scale (EPDS), among 877 pregnant women in early pregnancy and at one month postpartum. First, J-SSQ was standardized among peripartum women. The J-SSQ was found to have a two-factor structure, with Number and Satisfaction subscales, by exploratory and confirmatory factor analyses. Analysis of covariance was performed to examine how EPDS and J-SSQ scores during pregnancy affected the EPDS score at postpartum. Significant associations were found between postpartum EPDS score and both EPDS and total scores on the Number subscales during pregnancy (β = 0.488 and -0.054, ps < 0.001). Specifically, this negative correlation was stronger in depressive than non-depressive groups. Meanwhile, total score on Satisfaction subscales was not significantly associated with postpartum EPDS score. These results suggest that having a larger number of supportive persons during pregnancy helps protect against postpartum depression, and that this effect is greater in depressive than non-depressive pregnant women. This finding is expected to be vitally important in preventive interventions.